Faktor-Faktor yang Berhubungan dengan Keluhan Subjektif Non Auditory Pekerja Bagian Produksi Industri - Shalsa Eka Putri; Pangestika, Rismawati (Politeknik Baubau, 2024)
Continuous exposure to noise is one of the factors that can cause non-auditory subjective complaints in the form of communication disorders, physiological disorders and psychological disorders as well as causing hearing problems, namely deafness. If noise exposure lasts for a long period of time along with other factors it will produce discomfort for the workforce and will have a negative impact on their performance. Most of the non-auditory health impacts of noise are not realized by individuals. The use of technology-based machines is very practical but can produce side effects in the form of physical factors such as noise, vibration and radiation which have the potential to have a negative impact on work and working conditions. The aim of this research is to determine the factors related to non-auditory subjective complaints from workers in the production section of the Brumbung Perum Perhutani Semarang Wood Processing Industry in 2023. This research is Quantitative approach with Cross Sectional design. The data collection method used was through an interview process using a questionnaire. The population in this study was 63 people, and the sample was 63 people using total sampling techniques. Results Chi square test results showed a relationship between noise intensity, age, and APT compliance (Pvalue <0.05). This shows that there is a significant relationship between noise intensity (0.001), age (0.048), and APT compliance (0.007) with non-auditory subjective complaints in the Brumbung Wood Processing Industry, Semarang in 2023.